Cytochrome components of nitrate- and sulfate-respiring Desulfovibrio desulfuricans ATCC 27774. - Liu, M. C. (1988)
Three multiheme c-type cytochromes--the tetraheme cytochrome c3 (molecular weight [MW] 13,500), a dodecaheme cytochrome c (MW 40,800), and a "split-Soret" cytochrome c (MW 51,540), which is a dimer with 2 hemes per subunit (MW 26,300)--were isolated from the soluble fraction of Desulfovibrio desulfuricans (ATCC 27774) grown under nitrate- or sulfate-respiring conditions. Two of them, the dodecaheme and the split-Soret cytochromes, showed no similarities to any of the c-type cytochromes isolated from other sulfate-reducing bacteria, while the tetraheme cytochrome c3 appeared to be analogous to the cytochrome c3 found in other sulfate-reducing bacteria. For all three multiheme c-type cytochromes isolated, the homologous proteins from nitrate- and sulfate-grown cells were indistinguishable in amino acid composition, physical properties, and spectroscopic characteristics. It therefore appears that the same c-type cytochrome components are present when D. desulfuricans ATCC 27774 cells are grown under either condition. This is in contrast to the considerable difference found in Pseudomonas perfectomarina (Liu et al., J. Bacteriol. 154:278-286, 1983), a marine denitrifier, when the cells are grown on nitrate or oxygen as the terminal electron acceptor. In addition, two spectroscopy methods capable of revealing minute structural variations in proteins provided identical information about the tetraheme cytochrome c3 from nitrate-grown and sulfate-grown cells.